PENGARUH GAYA HIDUP HEDONIS TERHADAP PERILAKU KONSUMTIF PADA PRAMUGARI MASKAPAI PENERBANGAN âXâ - Patricia, Nesa Lydia; Handayani, Sri (Jurnal Psikologi, 2014)
AbstractAs a front liner ofan Airlines, the Flight Attendants are required to maintain their performance. Demands of the profession coupled with the desire to be an elegant appearance are driving the Flight Attendants to aconsumptivebehavior. One of the factors that purchase influence tothe flight attandantâs consumptive behavior is the hedonic lifestyle. This research was conducted to determine whether there is a positive influenceof the hedonic lifestyle to the consumptive behaviorÂ on the